EVALUATION OF DIFFERENT BRASSICA SPECIES AND ONION FOR THEIR BIOFUMIGATION EFFECT AGAINST Rhizoctonia solani f. sp. sasakii in vitro - G. BINDU MADHAVI, G. UMA DEVI , K. VIJAY KRISHNA KUMAR , T. RAMESH BABU AND T.C.M. NAIDU (The Journal of Research ANGRAU, 2015)
Glucosinolate-containing Brassica spp. is known to release volatilic isothiocyanates (ITCs) which are toxic todifferent pathogens. The chemistry involved in the biofumigation can be attributed to the action of myrosinases on theglucosinolates (GLS) thereby releasing ITCs, thiocyanates, nitriles, oxalidine, dimethyl sulphide, methanethiol amongother compounds.The present study was taken up to evaluate different Brassica spp and onion for their biofumigationeffect against Rhizoctonia solani f. sp. sasakii in vitro. Among different brassica species, macerated mustard plantparts are effective in inhibition of radial growth and sclerotial production of Rhizoctonia solani f. sp sasakii. In alltested concentrations there was a positive association between increase of volumes and the rate of radial growthsuppression.